Kebutuhan dan Perencanaan Tenaga Kesehatan di Provinsi Sumatera Utara - Heru Santosa (Center for Health Policy and Management, 2015)
Background: The health sector planning process regarding facilities, infrastructure and health work force is a planning document that contains information and data health development programs that will be implemented by the government. Thus the results of the study are expected to become the master development plan document for health sector in infrastructures and facilities as well as health professionals. This study was conducted to describe the supply of health personnel or whether the target has been reached, to calculate the need of health work force according to the number, types and qualifications, and to formulate policy regarding the needs of health work forcein North Sumatera Province. Methods: Methods for estimating health manpower needs was determined by the ratio method. The use of this method is based on the data and goal of study by focusing on the achievement so far and by comparing the ratio of the target. Results: Compared to 2010, the average estimated needs of health workers in 2015 was twice as much. This is a challenge that needs to get attention. It was caused by the limited budget to support recruitment and procurement. The results of the study also found that some types of health personnel were “rare” such as health analysts, speech therapists, refractionists optician, physio therapist, radiographer, epidemiology, and health planners.Conclusion: The empowerment program and the utilization of available health personnel with the addition of sufficient incentives was certainly more efficient than recruitment or procurement of new personnel, although the number of health professionals still should be added gradually every year. Latar Belakang: Upaya penyusunan perencanaan sektor ke- sehatan bidang sarana dan prasarana dengan tenaga kese- hatan merupakan dokumen perencanaan yang bersifat indikatif yang memuat informasi dan data program-program pemba- ngunan kesehatan yang akan dilaksanakan langsung oleh Pe- merintah. Dengan demikian hasil kajian diharapkan sebagai dokumen perencanaan induk pembangunan sektor kesehatan bidang prasarana dan sarana serta sumber daya tenaga kese- hatan. Mendasarkan hal tersebut maka kajian ini dilakukan untuk menggambarkan pencapaian atau penyediaan tenaga kese- hatan, menghitung kebutuhan tenaga kesehatan menurut jumlah, jenis dan kualifikasi dan merumuskan kebutuhan kebijakan perencanaan tenaga kesehatan di Provinsi Sumatera Utara. Metode:Metode penyusunan kebutuhan tenaga kesehatan ditentukan dengan metode rasio (Ratios Method). Penggunaan metode ini mendasarkan kepada data dan tujuan kajian yang lebih mengutamakan pencapaian dengan membandingkan terhadap rasio sebagai sasaran. Hasil: Dibandingkan tahun 2010, maka perkiraan rata-rata kebutuhan tenaga kesehatan pada tahun 2015 sebanyak dua kali lipatnya. Tentunya suatu tantangan yang perlu mendapatkan perhatiannya. Hal ini disebabkan oleh keterbatasan dukungan anggaran untuk melakukan rekruitmen dan pengadaan tenaga kesehatan secara berlebihan. Hasil kajian juga menemukan beberapa jenis tenaga kesehatan yang ”langka” seperti analis kesehatan, terapis wicara, refraksionis optisien, fisioterapis, radiographer, epidemiologi, dan ahli perencana kesehatan. Conclusion:Program pemberdayaan dan pendayagunaan tenaga kesehatan yang ada dengan penambahan insentif yang cukup tentunya lebih efisien bila dibandingkan rekruitmen atau pengadaan tenaga baru, walaupun secara bertahap tetap harus dilakukan penambahan setiap tahunnya.